Bestimmung und Taxonomie der paläarktischen Conopiden (Diptera). 2. Teil: Die Gattung Dalmannia Robineau-Desvoidy, 1830. - Stuke, Jens-Hermann (Contributions to Entomology = Beiträge zur Entomologie, 2007)
A key to the six Palaearctic species of the genus Dalmannia Robineau-Desvoidy, 1830 is presented. Two new synonymies are introduced (syn. n.): Dalmannia confusa Becker, 1923 = Dalmannia dorsalis (Fabricius, 1794) and Dalmannia aharonii Kröber, 1932 = Dalmannia marginata (Meigen, 1824). Keywords Diptera, Conopidae, Dalmannia, new synonyms, key, Palearctic region. Nomenclatural Acts aharonii Kröber, 1932 (Dalmannia), syn. n. of Dalmannia marginata (Meigen, 1824) confusa Becker, 1923 (Dalmannia), syn. n. of Dalmannia dorsalis (Fabricius, 1794)